Effects of voltage unbalanced supplies on energy-efficient motors - Van Wyk, Ashwill Louis (Department of Electrical Engineering, 2015)
Eskom DSM has recently introduced an Energy Efficiency (EE) Motor program, which provides incentives to industrial customers to retrofit standard motors with EE motors. The main objective of the program is to realize energy savings through the replacement of standard (STD) induction motors with higher efficiency EE motors. Although the principle of the program is correct, there are several significant power quality and performance issues with EE motors.These issues need to be thoroughly investigated in order to achieve the overall energy saving objectives of program.